The associations that income, education, and ethnicity have with birthweight and prematurity: how close are they? - Ana Daniela Izoton de Sadovsky; Keila Cristina Mascarello; Angelica Espinosa Miranda; Mariangela F. Silveira (Pan American Health Organization, 2018)
Objectives. To identify evidence that income, education, or ethnicity might be associated with low birthweight, small-for-gestational-age birth, or preterm birth. Methods. A systematic review was conducted using searches in two online databases, PubMed and Literature in the Health Sciences in Latin America and the Caribbean (LILACS). The searches covered materials published between 1 January 1982 and 5 May 2016. The search terms used were ("infant, premature" OR "infant, small for gestational age" OR "fetal growth retardation") AND ("socioeconomic factors" OR "ethnic groups" OR "maternal age"). Results. A total of 3 070 references that met the initial selection criteria were analyzed, and 157 relevant studies were fully read. We located 18 studies that investigated associations of family or maternal income, education, or ethnicity with low birthweight, small-for-gestational-age birth, or preterm birth. Of the 18, 10 of them involved high-income countries, and 8 dealt with middle- or low-income countries. Greater evidence was found for an association between ethnicity and the three outcomes studied, particularly for prematurity among children of black mothers. There was little evidence for an association between maternal/family income or education and any of the three outcomes. Conclusions. Income and education weren't determinants for low birthweight, small-for-gestational-age birth, or preterm birth. However, black ethnicity was strongly associated with the three outcomes, especially with prematurity.